2020
DOI: 10.3390/cells9081871
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Brain Injury, Antenatal Triggers, and Therapeutics: Timing Is Key

Abstract: With a worldwide incidence of 15 million cases, preterm birth is a major contributor to neonatal mortality and morbidity, and concomitant social and economic burden Preterm infants are predisposed to life-long neurological disorders due to the immaturity of the brain. The risks are inversely proportional to maturity at birth. In the majority of extremely preterm infants (<28 weeks’ gestation), perinatal brain injury is associated with exposure to multiple inflammatory perinatal triggers that include antenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 267 publications
(378 reference statements)
0
71
0
2
Order By: Relevance
“…Such prenatal insults are associated with infections just after birth (early onset sepsis, EOS) and altered immune system development with a range of adverse short- and longer-term outcomes across many organs (e.g., NEC, BPD, and IVH) [ 245 ]. The health consequences of fetal inflammation for preterm infants are highly dependent on the type, length and level of fetal infection-induced inflammation, from inducing a precocious (potentially beneficial) immune maturation, to adverse immune defects with subsequent widespread inflammatory insults [ 246 , 247 ]. No studies are available in infants but in theory, BC supplementation may ameliorate the postnatal consequences of fetal inflammation by better control of bacterial colonization after birth and modulation of local and systemic immune responses.…”
Section: Bovine Colostrum To Prevent or Treat Specific Pediatric Diseasesmentioning
confidence: 99%
“…Such prenatal insults are associated with infections just after birth (early onset sepsis, EOS) and altered immune system development with a range of adverse short- and longer-term outcomes across many organs (e.g., NEC, BPD, and IVH) [ 245 ]. The health consequences of fetal inflammation for preterm infants are highly dependent on the type, length and level of fetal infection-induced inflammation, from inducing a precocious (potentially beneficial) immune maturation, to adverse immune defects with subsequent widespread inflammatory insults [ 246 , 247 ]. No studies are available in infants but in theory, BC supplementation may ameliorate the postnatal consequences of fetal inflammation by better control of bacterial colonization after birth and modulation of local and systemic immune responses.…”
Section: Bovine Colostrum To Prevent or Treat Specific Pediatric Diseasesmentioning
confidence: 99%
“…Clinical presentation of injuries, as well as timing of the initial onset is often unclear and difficult to determine (Ophelders et al, 2020). This is especially apparent in the case of HI injuries, since observed latency for first appearance of seizures can vary from minutes to days following birth (Naeye and Lin, 2001).…”
Section: Summary Of Therapeutic Ev Studies In Experimental Animal Models Of Perinatal Brain Injurymentioning
confidence: 99%
“…First, the dHCP segmentation pipeline was developed based on 20 manually segmented infant brain scans; however, 15 of these were from infants born prematurely. Samples used in our work are born from full-term infants, and numerous previous studies have shown significant structural brain differences in pre-relative to full-term infants (Ment & Vohr, 2008;Ophelders et al, 2020). Second, MRI scans in our work were collected from multiple vendors, including GE, Siemens, and Philips, allowing ID-Seg to learn and adapt to the idiosyncratic features of specific MRI vendors.…”
Section: C 4d Blue Lines)mentioning
confidence: 99%